IMPLEMENTASI TOTAL QUALITY MANAGEMENT (TQM) DALAM UPAYA PENINGKATAN MUTU PENDIDIKAN SEKOLAH (Studi Kasus di SMK Islam Datuk Singaraja Kerso Kedung Jepara) - Subaidi Subaidi; Samidi Samidi (Balai Penelitian dan Pengembangan Agama Semarang, 2018)
This research described the implementation of Total Quality Management (TQM) in the efforts of improving education quality of the school in Vocational School of Datuk Singaraja Kerso Kedung Jepara. The purpose of this research is to know how far the efforts of improving education quality of school through implantation of Total Quality Management (TQM) in Vocational School of Datuk Singaraja Kerso Kedung Jepara. This research is descriptive qualitative research. The technique of analyzing data is descriptive analysis. The results of this research are; first, the school tries to complete students’, teachers’, and parents’ necessities and wishes; second, in creating the education quality school always gives response and take action of ideas and suggestions from all of side; third, the result of academic activities in Vocational School of Datuk Singaraja Kerso Kedung Jepara increase in the last 3 years, it is marked by students’ achievement in local and national level. Meanwhile the obstacles are; first, less synchronization of activity schedule from each domain; second, the centralistic financial system in institute; third, not all of the students live in dorm and Islamic dormitory that already prepared by the institute.